Structural and optical characteristics of disordered silicon carbide films - Lopin, A.V. (Functional Materials, 2008)
Using spectrophotometry and electron microscopy, the properties of disordered SiC films have been studied. A nontrivial character of spectral absorption has been revealed depending on the structural and polytype constitution of the films. SiC polytypes forming the film and the band gap widths have been determined. It has been shown that in this case, it is possible to obtain the information on the optical band-to-band transition modification depending on the film structure property and phase composition as well as on the influence of various phases and SiC film crystallinity extent on the band gap width.